Education against ageism, stereotypes and gerontophobia about the sexuality of older adults (development of a model for integrated promotion of sexual life of older adults) - Petek, Karmen (Medicine, law & society, 2025)
This study aims to develop an educational model and guidelines for promoting sexual health in older adults (55+), addressing ageism, stereotypes, and gerontophobia. Despite its significance for successful aging, sexual health in older adults is often neglected. The study involved 651 participants (aged 55-75) and used a quantitative approach, examining factors like health status, sexual activity, and education through an online survey. Key findings include a positive correlation between health and sexual satisfaction (r = 0.2 to 0.4, p < 0.001) and the importance of sexual knowledge in life satisfaction (F = 90.027; p < 0.001). Results underline the need for tailored educational programs and open discussions on sexuality. The proposed model aims to improve sexual well-being and overall quality of life, promoting a holistic approach to sexual health care to older adults. These findings are relevant for shaping policies and interventions in Slovenia and globally.
Keywords: activity; older adults; satisfaction; sexuality; stereotypes; withdrawal